2021
DOI: 10.2147/dmso.s326195
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Skeletal Muscle Mass to Visceral Fat Area Ratio and Cardiovascular Risk in Type 2 Diabetes

Abstract: Purpose Either visceral fat or muscle mass is identified to be correlated with cardiometabolic diseases, especially in type 2 diabetes (T2DM). But, the synergistical effect of visceral fat along with skeletal muscle on the risk of cardiovascular diseases (CVD) in T2DM still remains controversial. Thus, we investigated the relationship between skeletal muscle mass to visceral fat area ratio (SVR) and 10-yr CVD risk scores. Patients and Methods A total of 291 T2DM patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Several studies have pointed out that BMI and WC do not perform satisfactorily for estimating visceral fat function and distribution. 46,47 To address this issue, researchers have developed the CVAI for the metabolic characteristics of the Chinese population to more accurately assess the visceral fat distribution and cardiometabolic risk in specific populations. 25,37 Initially, CVAI was deemed to be a reliable surrogate for assessing metabolic health and predicting diabetes.…”
mentioning
confidence: 99%
“…Several studies have pointed out that BMI and WC do not perform satisfactorily for estimating visceral fat function and distribution. 46,47 To address this issue, researchers have developed the CVAI for the metabolic characteristics of the Chinese population to more accurately assess the visceral fat distribution and cardiometabolic risk in specific populations. 25,37 Initially, CVAI was deemed to be a reliable surrogate for assessing metabolic health and predicting diabetes.…”
mentioning
confidence: 99%
“…VFA was adjusted by weight (VFA/weight, cm 2 /kg), which was defined as the visceral fat index (VFI) [ 23 ]. The skeletal muscle mass to VFA ratio (SVR) was calculated as ASM (kg) divided by VFA (cm 2 ) [ 24 ]. Since there are no standardized cut-off values for these indices, all indices were divided into quartiles and analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Park et al [50] showed that low appendiceal skeletal muscle mass and low grip strength are closely related to cardiovascular disease and coronary heart disease in T2DM. Liu et al [51] reported that skeletal muscle mass and visceral fat area ratio were negatively correlated with 10-year cardiovascular disease risk in T2DM patients, especially in patients with high HbA1c levels.…”
Section: Influencing Factors Related To Sarcopenia In Patients With T2dmmentioning
confidence: 99%